Integrating Positive Psychology into Substance Use Treatments - Bryant M. Stone (Encyclopedia, 2023)
Positive psychology is a rapidly expanding and recent empirical. interdisciplinary research topic (i.e., within the last 25 years). Early evidence supported that targeting positive variables (i.e., empathy or kindness) has numerous benefits, including improving health outcomes, vocational success, psychological well-being, and interpersonal connectedness. Positive Psychological Interventions (PPIs) are activities and behavioral interventions that target positive variables to promote adaptive functioning (e.g., reducing depression or promoting psychological well-being). PPIs may make excellent contributions to treating substance use, substance use disorders (SUDs), and substance use problems because the interventions can partially shift the notable negative treatment focus (e.g., avoiding the consequences of using) onto positive aspects (e.g., pursuing an ideal future). Current substance use treatment outcomes demonstrate a need for improvements (e.g., low abstinence rates and lifetime symptom remission of SUDs), and positive psychology may provide a framework for improving existing treatments. In the current paper, the author reviewed research supporting the use of PPIs in substance use treatments, provide suggestions for PPI applications, examine advantages and practical issues, outline the current limitations, and provide future directions for continuing this line of work. The author aimed to encourage researchers to advance substance use treatment improvements with positive psychology because the growing consequences from substance use (e.g., the growing frequency of accidental fatal overdose) and the variable, limited treatment outcomes, placing those who use substances in a uniquely vulnerable position.